Long‐lived mesoscale eddies in the eastern Mediterranean Sea: Analysis of 20 years of AVISO geostrophic velocities. Issue 12 (16th December 2014) - Mkhinini, Nadia; Coimbra, Andre Louis Santi; Stegner, Alexandre; Arsouze, Thomas; Taupier‐Letage, Isabelle; Béranger, Karine
Abstract We analyzed 20 years of AVISO data set to detect and characterize long‐lived eddies, which stay coherent more than 6 months, in the eastern Mediterranean Sea. In order to process the coarse gridded ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3gsrvnnd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1/8°</alternatives>) AVISO geostrophic velocity fields, we optimized a geometrical eddy detection algorithm. Our main contribution was to implement a new procedure based on the computation of the Local and Normalized Angular Momentum (LNAM) to identify the positions of the eddy centers and to follow their Lagrangian trajectories. We verify on two mesoscale anticyclones, sampled during the EGYPT campaign in 2006, that our methodology provides a correct estimation of the eddy centers and their characteristic radius corresponding to the maximal tangential velocity. Our analysis reveals the dominance of anticyclones among the long‐lived eddies. This cyclone‐anticyclone asymmetry appears to be much more pronounced in eastern Mediterranean Sea than in the global ocean. Then we focus our study on the formation areas of long‐lived eddies. We confirm that the generations of the Ierapetra and the Pelops anticyclones are recurrent and correlated to the Etesian wind forcing. We also provide some evidence that the smaller cyclonic eddies formed at the southwest of Crete may also be induced by the same wind forcing. On the other hand, the generation of long‐lived eddies along the Libyo‐Egyptian coast are not correlated to the local wind‐stress curl but surprisingly, their initial formation points follow the Herodotus Trough bathymetry. Moreover, we identify a new formation area, not discussed before, along the curved shelf off Benghazi.